Bacillus subtilis Probiotics in Chicken Feed Improve Egg Quality with Differences in Shelf Life - Wardiana, Nurul Ika; Lokapirnasari, Widya Paramita; Harijani, Nenny; Al-Arif, Mohammad Anam; Ardianto, Ardianto (Jurnal Medik Veteriner, 2021)
This study aims to examine the effect of giving Bacillus subtilis probiotics in laying hens on improving the quality of internal and external eggs with differences in shelf life. A total of 60 laying hens were divided into 4 treatment groups, namely P0 as a control that was not given probiotic B. Subtilis, P1 feed was added 0.005 grams B. Subtilis, P2 feed with added 0.01 grams B. Subtilis, P3 feed added 0.02 grams B. Subtilis then the eggs produced are stored for 1 day, 5 days and 10 days. The results of this study indicate that the administration of B. Subtilis probiotics with a concentration of 0.02 grams affects the increase in egg weight, egg yolk index value and HU values. The addition of B. Subtilis probiotics to racial feed can improve egg quality.